Managerial Capability and Financial Sustainability of SMEs: The Mediating Role of Product Innovation and the Moderating Role of Access to Finance - Duduh Sujana; Nugraha Nugraha; Disman Disman; Imas Purnamasari (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Financial sustainability is a decisive condition for small and medium-sized enterprises (SMEs) because it determines whether firms can maintain liquidity, generate stable profitability, absorb shocks, and finance growth. Drawing on Dynamic Capability Theory and the Resource-Based View, this study examines how managerial capability contributes to SME financial sustainability through product innovation and how access to finance strengthens the innovation-sustainability relationship. The research used a quantitative survey design involving 350 SME owners and managers in West Java, Indonesia, selected through purposive sampling. Data were collected using a structured seven-point Likert questionnaire and analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that managerial capability has a strong positive effect on product innovation (beta = 0.727; t = 19.755; p < 0.001), product innovation positively affects financial sustainability (beta = 0.411; t = 4.876; p < 0.001), and managerial capability directly improves financial sustainability (beta = 0.231; t = 5.422; p < 0.001). Product innovation significantly mediates the effect of managerial capability on financial sustainability (indirect effect = 0.299; t = 5.742; p < 0.001), while access to finance positively moderates the effect of product innovation on financial sustainability (beta = 0.218; t = 3.108; p = 0.002). The findings support a Dynamic Capability-Based Financial Sustainability Model for SMEs, suggesting that managerial capability becomes financially meaningful when translated into innovation and supported by adequate financial access. The study contributes to strategic management, entrepreneurship, and SME sustainability literature by clarifying the capability-innovation-finance mechanism through which SMEs improve long-term financial viability in an emerging economy context.   Keywords: managerial capability; product innovation; access to finance; financial sustainability; SMEs; dynamic capability; PLS-SEM